2004
DOI: 10.1073/pnas.0408260101
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of epithelial cells microscopically isolated from a breast-invasive ductal carcinoma and a nodal metastasis

Abstract: Expression profiles of breast carcinomas are difficult to interpret when they are obtained from tissue in toto, which may contain a large proportion of non-cancer cells. To avoid this problem, we microscopically isolated cells from a primary invasive ductal carcinoma of the breast and from an axillary node harboring a metastatic breast carcinoma, to obtain pure populations of carcinoma cells (Ϸ500) and used them for serial analysis of gene expression. The expression profiles generated from both populations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
1
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 41 publications
1
69
1
1
Order By: Relevance
“…Remarkably, we could find less upregulated genes in the liver metastases than in the primary tumour, indicating a possible loss of regulating and tumour suppressor genes. The same observation has been made by other groups Zucchi et al, 2004). Zucchi et al (2004) hypothesised that the downregulation of a set of genes may be the basic mechanism of cancer formation, whereas the upregulation may characterise and possibly control the state of evolution of individual cancers.…”
Section: Discussionsupporting
confidence: 48%
“…Remarkably, we could find less upregulated genes in the liver metastases than in the primary tumour, indicating a possible loss of regulating and tumour suppressor genes. The same observation has been made by other groups Zucchi et al, 2004). Zucchi et al (2004) hypothesised that the downregulation of a set of genes may be the basic mechanism of cancer formation, whereas the upregulation may characterise and possibly control the state of evolution of individual cancers.…”
Section: Discussionsupporting
confidence: 48%
“…Our detection of ODAM in other epithelial malignancies, for example, breast, lung, and gastric cancers, also suggests that this protein is up-regulated in these cancers. Interestingly, the FDC-SP gene, adjacent to ODAM in the SCPP cluster, is expressed in late dental development, as well as in neoplasms of the breast; further, it has been included as a gene signature screening component indicative of breast cancer invasiveness (19,34,35). In the case of colon cancer, this neoplasm results from a progressive series of steps whereby epithelial dysplasia evolves into a flat adenoma, carcinoma in situ, and finally, adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has recently been suggested that Emilin2, which encodes the elastin microfibril interfacer 2, is subject to DNA methylation leading to reduced gene expression in human breast cancers, and Emilin2 hypermethylation is associated with poorer clinical outcome, in particular relapse and poor survival (33). Last, elevated expression of Spdya (also known as Spy1), which encodes the speedy homolog A, accelerates tumorigenesis in a mouse model of breast cancer (34) and has also been associated with more aggressive human breast cancers (35). As such, other genes in this locus merit future investigation.…”
Section: Discussionmentioning
confidence: 99%